To Do This, You Must Know How : Music Pedagogy in the Black Gospel Quartet Tradition - Abbott, Lynn, 1946- (Book collections on Project MUSE., 2013)
This study traces black vocal music instruction and inspiration from the halls of Fisk University to the mining camps of Birmingham and Bessemer, Alabama, and on to Chicago and New Orleans. In the 1870s, the Original Fisk University Jubilee Singers successfully combined Negro spirituals with formal choral music disciplines. Early in the twentieth century there were countless initiatives in support of black vocal music training conducted on both national and local levels. The surge in black religious quartet singing that occurred in the 1920s owed much to this vocal music education movement.